Implementation of School Literacy Program In Junior High School Muhammadiyah Palangka Raya - Feri Wagiono; Offeny Offeny; Eli Karliani (Universitas of Muhammadiyah Makassar, 2020)
Abstract. This research on implementing school literacy programs, supporting factors, and inhibiting the implementation of school literacy program students and solutions are done by the school in overcoming the barriers to implementation of the Student literacy program in SMP Muhammadiyah Palangka Raya. The culture of reading through school literacy is a step in the student's character growth. This research uses qualitative methods, based on the fact that goes on now. Data collection techniques using interviews, observations, and documentation. Data analysis techniques used are data reduction, data presentation then draw conclusions or data verification. The results of the authors ' research led to the conclusion that: (1) Implementation of school literacy phase of habituation is 15 minutes reading non-book lessons, the development stage is to increase the reading ability by analyzing the books read, the learning stage is followed by analyzing and providing academic bills and increase the confidence of students through habituation and vigorous reading that was programmed by SMP Muhammadiyah Palangka Raya, (2) supporting factors and inhibitors of literacy activities in SMP Muhammadiyah Palangka Raya, infrastructure facilities, book library facility adequate, book donation of parents, teachers, and alumni, students are still minimal culture reading and late to class, (3) The solution motivates the students to follow the activities well, give direction or rebuke, appealed to all the school citizens whether teachers or students to love reading and writing to be a literate person.Keywords: Implementation, School literacy of programs, SMP Muhammadiyah Palangka RayaAbstrak. Penelitian ini tentang implementasi program Literasi Sekolah, faktor pendukung dan penghambat implementasi program Literasi Sekolah siswa dan solusi dilakukan pihak sekolah dalam mengatasi hambatan implementasi program literasi siswa di SMP Muhammadiyah Palangka Raya. Pembudayaan membaca melalui Literasi Sekolah menjadi suatu langkah dalam penumbuhan budi pekerti siswa. Penelitian ini menggunakan metode kualitatif, didasarkan atas kenyataan yang berlangsung sekarang. Teknik pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Teknik analisis data yang digunakan yaitu reduksi data, penyajian data kemudian penarikan kesimpulan atau verifikasi data. Hasil penelitian penulis mengarah kepada kesimpulan yaitu: (1) implementasi literasi sekolah tahap pembiasaan yaitu 15 menit membaca buku non-pelajaran, tahap pengembangan yaitu meningkatkan kemampuan membaca dengan menganalisis buku yang dibaca, tahap pembelajaran yaitu dilanjutkan dengan menganalisis serta pemberian tagihan akademik dan meningkatkan kepercayaan diri siswa melalui pembiasaan dan giat membaca yang diprogramkan oleh SMP Muhammadiyah Palangka Raya, (2) Faktor pendukung dan penghambat kegiatan literasi di SMP Muhammadiyah Palangka Raya, sarana prasarana, fasilitas buku perpustakaan memadai, progam sumbangan buku dari orang tua, guru dan alumni, siswa masih minim budaya membaca dan terlambat ke kelas, (3) Solusi memotivasi siswa mengikuti kegiatan dengan baik, memberikan arahan atau teguran, menghimbau kepada seluruh warga sekolah baik guru atau siswa untuk gemar membaca dan menulis agar menjadi pribadi yang literat.Kata Kunci: Implementasi, Program Literasi Sekolah, SMP Muhammadiyah Palangka Raya